1994
DOI: 10.1002/j.1460-2075.1994.tb06723.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct mechanisms contribute to the constitutive activation of RelB in lymphoid cells.

Abstract: The KB-motif is an important regulatory element both for constitutive lymphoid-specific as well as ubiquitous inducible transcriptional activity. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 66 publications
4
73
1
Order By: Relevance
“…Previous studies stated that, while IkB-a or IkB-b mostly controlled the activity of NF-kB-p50/p65 complexes and IkB-e associated preferentially with cRel and p65, p100 regulated the activity of RelBcontaining complexes (Dobrzanski et al, 1994(Dobrzanski et al, , 1995Lernbecher et al, 1994). However, the present report demonstrates that p100, when highly expressed in adenocarcinoma cells, also sequestered most of p65 complexes in the cytoplasm.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies stated that, while IkB-a or IkB-b mostly controlled the activity of NF-kB-p50/p65 complexes and IkB-e associated preferentially with cRel and p65, p100 regulated the activity of RelBcontaining complexes (Dobrzanski et al, 1994(Dobrzanski et al, , 1995Lernbecher et al, 1994). However, the present report demonstrates that p100, when highly expressed in adenocarcinoma cells, also sequestered most of p65 complexes in the cytoplasm.…”
Section: Discussioncontrasting
confidence: 56%
“…It was indeed demonstrated that p100 can form cytoplasmic complexes with p65, p50 and RelB (Mercurio et al, 1993;Scheinman et al, 1993;Kanno et al, 1994;Dejardin et al, 1995). Previous reports indicated that RelB complexes poorly interact with IkB-a, p105 or Bcl-3 and are preferentially inhibited by p100 in B lymphocytes (Lernbecher et al, 1994;Dobrzanski et al, 1994Dobrzanski et al, , 1995. Our data con®rm that, in breast cancer cells, RelB-containing complexes are not inhibited by IkB-a but by p100, indicating a preferential interaction between RelB and the IkB-like molecule p100.…”
Section: Discussionmentioning
confidence: 93%
“…Several mechanisms contribute to constitutive nuclear NF-KB expression. An increased turnover of IKBa (Miyamoto et al, 1994a), a selective change in the susceptibility in lymphoid tissue of RelB to inhibition by IKBa (Lernbecher et al, 1994), and differential affinities of various NF-KB/Rel dimers for IKBa (Dobrzanski et al, 1994) have all been demonstrated. Since a large proportion of the constitutive activity in these cells is accounted for by p50-containing species, the requirements for NFKB1 synthesis may be different than those in other cell types.…”
Section: Discussionmentioning
confidence: 99%